FOXL2 directs DNA double-strand break repair pathways by differentially interacting with Ku - Hanyong Jin (Nature Portfolio, 2020)
The Ku complex, formed by XRCC5/6 heterodimer, binds to double strand break (DSB) ends, initiating non homologous end joining (NHEJ) and preventing homologous recombination (HR). Here, the authors reveal that FOXL2, a forkhead family transcriptional factor, directs DSB repair pathway choice by acetylation-dependent binding to Ku.